1986
DOI: 10.1038/hdy.1986.11
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability in natural populations of Hawaiian Drosophila. I. Methods and levels of variability in D. silvestris and D. heteroneura populations

Abstract: We describe techniques by which mitochondrial DNA (mtDNA) restriction site information can be obtained for up to 16 different restriction endonucleases on individual Hawaiian Drosophila, in particular D. silvestris and D. heteroneura. We have constructed mtDNA restriction site maps for a total of forty-eight wild caught genomes of both species, from seven major collecting sites on the island of Hawaii. Levels of variability are, in general, high in D. silvestris (p of Ewens et al., 1981 = 0.0486) and lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 44 publications
2
12
1
Order By: Relevance
“…Sequence divergences between H. irritans and H. exigua (1.8ῌ1.9ῌ) in the present study are larger than the range of the estimated values for intraspecies di#eren-tiation based on mtDNA in various insect species which have been reported by DeSalle et al (1986), Martin and Simon (1990), and Vargas and Espin (1995). mtDNA analysis of haplotypes of the calliphorid flies Chrysomya albiceps and C. rufifacies (which are closely related to each other) showed 0.04ῌ0.8ῌ intraspecies di#erences and 2.9ῌ3.1ῌ interspecies di#erences (Wells and Sperling, 1999).…”
Section: D>h8jhh>dccontrasting
confidence: 50%
“…Sequence divergences between H. irritans and H. exigua (1.8ῌ1.9ῌ) in the present study are larger than the range of the estimated values for intraspecies di#eren-tiation based on mtDNA in various insect species which have been reported by DeSalle et al (1986), Martin and Simon (1990), and Vargas and Espin (1995). mtDNA analysis of haplotypes of the calliphorid flies Chrysomya albiceps and C. rufifacies (which are closely related to each other) showed 0.04ῌ0.8ῌ intraspecies di#erences and 2.9ῌ3.1ῌ interspecies di#erences (Wells and Sperling, 1999).…”
Section: D>h8jhh>dccontrasting
confidence: 50%
“…It appears from mtDNA restriction sites that hybridisation of D. silvestris and D. heteroneura may have occurred on the west side of Hawaii (DeSalle et a!., 1985). In accordance with the mtDNA data, suspected hybrids of these two species have indeed been taken in the field at a west side collecting site (Kaneshiro and Val, 1977).…”
Section: S3s2s1 H5116h7s8s3 L14s253supporting
confidence: 54%
“…No fixed isozyme variants nor fixed chromosomal inversions have been found (Carson, 1983). Hunt and Carson (1982) have shown that a small but significant amount of single copy nuclear DNA sequence variation exists (0.6 per cent) and we (DeSalle et a!., 1985) have shown the existence of substantial mtDNA restriction site variability. Restriction site analysis of mtDNA may hence be useful in the genetic analysis of these species.…”
Section: Introductionmentioning
confidence: 98%
“…DNA manipulation and restriction site mapping were as described (18). The (16) or are available on request from the authors.…”
Section: Methodsmentioning
confidence: 99%